2004
DOI: 10.1002/anie.200460566
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ag2S Nanocrystals of Predictable Shape and Size

Abstract: In control! Ag2S nanocrystals of predictable size and shape were synthesized from the precursor Ag(SCOPh) in the presence of an amine. Careful tuning of several parameters, such as the reaction temperature and the ratio of amine to precursor, led to Ag2S nanocrystals of varying morphology (red: nanocubes; blue: faceted nanocrystals; yellow: nanorods) and size. x=particle size. HDA=hexadecylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(116 citation statements)
references
References 34 publications
3
112
0
1
Order By: Relevance
“…These are, for example, excellent layer uniformity, composition, and phase control, low cost, scalability, [6] and facile development of metallic nanoparticles in organic-inorganic hybrid matrices. [22] However, to the best of our knowledge, there is only a limited number of single-source precursors, such as [Ag(SC(O)Ph)] n , [20,23] [Ag 3 ((SPiPr 2 ) 6 N 3 )] 2 , [21] and [Ag(S 2 CNEt 2 )] n , [6] described in the literature for the generation of silver sulfide. This prompted us to synthesize novel silver(I) dithiocarbamates of the type [Ag{S 2 CNR(C 2 H 4 OH)}] (R = Me, Bu) and use them as single-source precursors for the formation of silver(I) sulfide.…”
Section: Introductionmentioning
confidence: 99%
“…These are, for example, excellent layer uniformity, composition, and phase control, low cost, scalability, [6] and facile development of metallic nanoparticles in organic-inorganic hybrid matrices. [22] However, to the best of our knowledge, there is only a limited number of single-source precursors, such as [Ag(SC(O)Ph)] n , [20,23] [Ag 3 ((SPiPr 2 ) 6 N 3 )] 2 , [21] and [Ag(S 2 CNEt 2 )] n , [6] described in the literature for the generation of silver sulfide. This prompted us to synthesize novel silver(I) dithiocarbamates of the type [Ag{S 2 CNR(C 2 H 4 OH)}] (R = Me, Bu) and use them as single-source precursors for the formation of silver(I) sulfide.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In particular, the shape-controlled synthesis of colloidal nanocrystals of metal chalcogenide semiconductors, such as cadmium chalcogenides, [1a,b,2] lead chalcogenides, [3] Ag 2 S, [4] and MnS, [3b,5] has attracted intensive interest; in this regard, synthetic methods based on high-temperature (typically 120-360°C) reactions in organic solutions involving capping agents have most often been employed. Although this hightemperature organic solution approach has been demonstrated to be a promising method for achieving morphological control of semiconductor nanocrystals, low-temperature synthesis in aqueous solutions is highly desirable because it represents an environmentally benign and user-friendly approach, which may be considered to be a relatively green chemical alternative of practical significance.…”
mentioning
confidence: 99%
“…It has been reported that Ag ions diffuse readily among the interstitial sites and thus lead to a facile morphological transformation [47]. Therefore, it is reasonable for Ag 2 S nanocrystals with monoclinic phase to take on a shape of cube under proper conditions and cubic α-Ag 2 S nanocrystals have also been obtained by thermolysis of organometallic complexes [37,38]. Further decrease of the ratio of [Tu] to [AgNO 3 ] to 1:1, the growth rate of 111 direction is further accelerated, resulting in the majority of the product is nanocubes with smaller size of 30-50 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, polyhedral nanocrystals including nanocubes have attracted intensive attention and a variety of faceted and cubic inorganic nanocrystals [26][27][28][29][30][31][32][33][34][35][36] have been successfully fabricated. Faceted and cubic Ag 2 S nanocrystals were also been prepared by Lim et al [37] and Wang et al [38] by decomposing exothermically organometallic precursor silver thiobenzoate (Ag(SCOPh)) and Ag[S 2 P(OR) 2 ] (R = C n H 2n+1 ), respectively. However, this kind of method often suffers from elaborate preparation of air-sensitive, expensive organometallic complexes that unstable in air, and also the use of high temperatures as well as the protection of inert gases, even the need of coordinating solvent.…”
Section: Introductionmentioning
confidence: 99%